Analisis Pengaruh Penggunaan Aplikasi Food Delivery Services Terhadap Penjualan UKM Di Masa Pandemi COVID-19 (Studi Pada Kota Bandung) - Alinda Devi Sofia; Septhara Adhityo Rohman; Harmon Chaniago (Asosiasi Ahli Administrasi Indonesia, 2021)
The COVID-19 pandemic that is currently striking has forced some businesses to reduce their business activities and some even have to close their businesses. One of the businesses that is directly affected is the culinary field of Small and Medium Enterprises. However, the application of food delivery services is like an oasis for business people, people still use this service to fulfil their needs. The purpose of this study was to see how much influence the use of food delivery services applications for Small and Medium Enterprises during the COVID-19 pandemic. The method used in simple linear regression analysis.